PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DAN MOTIVASI TERHADAP HASIL BELAJAR DAN BERPIKIR KRITIS SISWA - Maria Barus; Hasratuddin Hasratuddin; Anita Yus (JURNAL TEMATIK, 2019)
This research is motivated by the science learning outcomes are still far below the KKM value, learning models that have not been able to make students active, independent, and can develop knowledge from learning outcomes in class, students do not have the ability to think critically and students' low motivation to learn. This research was conducted on Grade VI students of SD Sudirman Medan which aims to find out: (1) The effect of PBL learning models on students 'science learning outcomes: (2) The effect of learning motivation on students' science learning outcomes; (3) The effect of learning motivation on students' critical thinking skills; (4) The effect of PBL learning models on students' critical thinking skills; (5) The effect of the interaction of PBL learning models and learning motivation on students 'science learning outcomes: (6) The effect of the interaction of PBL learning models and learning motivation on students' critical thinking skills. The sample technique in this study was conducted by cluster random sampling of two classes, class VI1 of 30 students as a control class with PBL learning models and class VI2 as a control class of 30 students who were taught with conventional learning models